The impact of transport infrastruture in the econolic growth of South Africa - Selamolela, Nokuthula (Graduate School of Business (GSB), 2018)
This study examines the impact of transport infrastructure on the economic growth of South Africa from the period 1970 to 2015. The researcher adopted a conceptual and theoretical framework related to infrastructure development and economic growth. The Johansen multivariate Co-integration and Granger causality test were adopted, consisting of stationary and directional causality of variables. The findings disclosed a strong unidirectional causality relationship in the long run between economic growth and gross domestic fixed capital formation, which runs from the former to the latter. The results also indicated a causal relationship between economic growth and transport infrastructure in both railway and ports transport. Moreover, there exist links between economic growth and railway transport, which run from the former to the latter. The findings further showed that the correlation between economic growth and ports transport runs from the former to the latter. On the contrary, the findings revealed a non-existence of causal relationship between economic growth and transport infrastructure (roadways and airways), though the theoretical framework demonstrates a link between them. The findings also revealed a non-existence of a causality association between economic growth and transport infrastructure performance. The overall findings demonstrated the existence of a unidirectional causality relationship between economic growth and gross domestic fixed capital formation, and between economic growth and transport infrastructure (both railways and ports transport). Economic growth expands commercial and industrial sectors and as such, there is a need to suggest that transport infrastructure development policies align with it to maintain sustainable economic growth in South Africa.